Investigation of the Best Approach for Assessing Human Exposure to Poly- and Perfluoroalkyl Substances through Indoor Air - Padilla-Sánchez, Juan A; Papadopoulou, Eleni; Poothong, Somrutai; Haug, Line S (Environmental science & technology, 2017)
Per- and polyfluoroalkyl substances (PFASs), including fluorotelomer alcohols (FTOHs), perfluoroalkyl sulfonamidoethanols (FOSEs), and perfluoroalkyl sulfonamides (FOSAs), were assessed in 61 residential indoor air and 15 personal air samples collected in Oslo area, Norway. FTOHs were detected in all samples, and the median concentrations in residential indoor air were 2970, 10400, and 3120 pg m for 6:2, 8:2, and 10:2 FTOH, respectively. This is similar to or higher than previously reported in studies from the same geographical area and worldwide. FOSEs and FOSAs were detected in 49-70% and 7-13% of the residential indoor air samples, respectively. The median FTOH concentrations observed in personal air were 1970, 7170, and 1590 pg m for 6:2, 8:2, and 10:2 FTOH, respectively, which is 30 to 50% lower than the median concentrations in residential indoor air. No FOSEs or FOSAs were detected above the method detection limit (MDL) in the personal air samples. Intakes of perfluorohexanoate (PFHxA), perfluoroheptanoate (PFHpA), perfluorooctanoate (PFOA), perfluorononanoate (PFNA), perfluorodecanoate (PFDA), perfluoroundecanoate (PFUnDA), and perfluorooctyl sulfonate (PFOS) through inhalation and biotransformation of PFAS precursors in air were estimated. Median intakes of 1.7, 0.17, 5.7, 0.57, 1.8, 0.18, and 2.3 pg kg bw day were obtained in residential indoor air, while 1.0, 0.10, 3.3, 0.33, 0.88, and 0.09 pg kg bw day were found in personal air for PFHxA, PFHpA, PFOA, PFNA, PFDA, PFUnDA, and PFOS, respectively. The median PFOA intakes from residential indoor air (5.7 pg kg bw day ) and personal air (3.3 pg kg bw day ) were both around 5 orders of magnitude lower than the tolerable daily intake (TDI) reported by the European Food Safety Authority (EFSA).